Development of Differentiated Teaching Materials Based on Prior Knowledge to Improve Mathematics Learning Outcomes of Junior High School Students - Dwi Maryani; Mardiyana Mardiyana; Riyadi Riyadi (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2026)
Classrooms in Indonesian junior secondary schools increasingly comprise students with diverse levels of prior mathematical knowledge, creating challenges for teachers in providing instruction that accommodates different learning needs. The availability of differentiated teaching materials is therefore essential for supporting effective implementation of differentiated instruction within the Merdeka Curriculum. This study aimed to develop differentiated teaching materials based on students' prior mathematical knowledge and to evaluate their validity, practicality, and effectiveness in improving mathematics learning outcomes on the topic of Flat-Sided Solid Figures. The study employed a Research and Development (R&D) approach using the ADDIE instructional design model. Three series of teaching materials were developed to accommodate students with low, moderate, and high levels of prior mathematical knowledge while maintaining common learning objectives. The validity of the materials was evaluated by three experts in mathematics content, language, and educational media. Practicality was assessed through teacher and student response questionnaires, whereas effectiveness was examined using a quasi-experimental Nonequivalent Control Group Design involving 63 Grade 8 students (experimental group, n = 31; control group, n = 32). The differentiated teaching materials achieved an overall validity score of 4.23 (Very Valid). Practicality evaluation indicated positive responses from students (79.92%; Practical) and teachers (85.27%; Very Practical). The effectiveness test showed that students in the experimental group achieved significantly higher mathematics learning outcomes than those in the control group (t = 2.976 > tcritical = 1.670, α = 0.05). The findings indicate that differentiated teaching materials based on students' prior mathematical knowledge provide a valid, practical, and effective instructional resource for supporting differentiated mathematics instruction in Indonesian junior secondary schools.